Cerebrospinal fluid and plasma distribution of anti-α-synuclein IgMs and IgGs in multiple system atrophy and Parkinson's disease. (June 2021) - Folke, Jonas; Rydbirk, Rasmus; Løkkegaard, Annemette; Hejl, Anne-Mette; Winge, Kristian; Starhof, Charlotte; Salvesen, Lisette; Pedersen, Lars Østergaard; Aznar, Susana; Pakkenberg, Bente; Brudek, Tomasz
Abstract: Introduction: Ubiquitous naturally occurring autoantibodies (nAbs) against alpha-synuclein (α-syn) may play important roles in the pathogenesis of Multiple System Atrophy (MSA) and Parkinson's disease (PD). Recently, we reported reduced high-affinity/avidity anti-α-syn nAbs levels in plasma from MSA and PD patients, along with distinct inter-group immunoglobulin (Ig)G subclass distributions. The extent to which these observations in plasma may reflect corresponding levels in the cerebrospinal fluid (CSF) is unknown. Methods: Using competitive and indirect ELISAs, we investigated the affinity/avidity of CSF anti-α-syn nAbs as well as the CSF and plasma distribution of IgG subclasses and IgM nAbs in a cross-sectional cohort of MSA and PD patients. Results: Repertoires of high-affinity/avidity anti-α-syn IgG nAbs were reduced in CSF samples from MSA and PD patients compared to controls. Furthermore, anti-α-syn IgM nAb levels were relatively lower in CSF and plasma from MSA patients but were reduced only in plasma from PD patients. Interestingly, anti-α-syn IgG subclasses presented disease-specific profiles both in CSF and plasma. Anti-α-syn IgG1, IgG2 and IgG3 levels were relatively increased in CSF of MSA patients, whereas PD patients showed increased anti-α-syn IgG2 and reduced anti-α-syn IgG4 levels. Conclusions: Differences in the plasma/CSF distribution of anti-α-syn nAbs seem to be a common feature of synucleinopathies. Our data add further support to the notion that MSA and PD patients may have compromised immune reactivity towards α-syn. The differing α-syn-specific systemic immunological responses may reflect their specific disease pathophysiologies. These results are encouraging for further investigation of these immunological mechanisms in neurodegenerative diseases. Highlights: Reduced high-affinity/avidity anti-α-synuclein nAbs in the CSF of MSA and PD patients compared to controls. Decreased anti-α-synuclein IgM nAbs in CSF and plasma of MSA patients and in CSF only of PD patients compared to controls. Distinct anti-α-synuclein IgG subclass nAb patterns in MSA and PD patients, suggest disease-specific immune responses.